Novel biogenic preparation of gold nanoparticles decorated on sepiolite clay and evaluation of anti-cancer effect on gastric cancer cell and electrochemical sensing of nitrite - Huang, Yakai; Zhang, Yingjing; Zhang, Yu; Liu, Wenping; Fang, Yantian; Motlagh, Masoud (Environmental research, 2023)
An environmentally friendly strategy was used in this study to synthesize gold nanoparticles decorated on sepiolite clay (GNPs-SC) using Heracleum persicum grass extract. The physicochemical characters of the prepared composite were characterized using transmission electron microscopy (TEM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). A GNPs-SC modified carbon pate electrode (CPE) was used to study the electrochemical oxidation of nitrite. The proposed nitrite sensor exhibits excellent performance, including a broad linear range (1.0–150 μM), a low limit of detection (0.4 μM), and acceptable reproducibility (RSD = 2.6%). As well, the prepared GNPs-SC was tested for its effectiveness against human gastric adenocarcinoma (AGS) cell line. The MTT assay protocol revealed that the bio-synthesized product displayed significant cytotoxic activity against gastric cancer in human subjects. The findings of this study indicate that GNPs-SC, synthesized using environmentally friendly protocol, exhibit great potential for use in electrochemical sensing and treatment of human cancer. [Display omitted] •Gold nanoparticles decorated on sepiolite clay were prepared using non-toxic green strategy.•A remarkable anticancer property was observed against the human gastric adenocarcinoma (AGS) cell line.•The fabrication of an effective electrochemical sensor for nitrite detection was achieved using the GNPs-SC.